2017
DOI: 10.1111/jspn.12174
|View full text |Cite
|
Sign up to set email alerts
|

The health‐related quality of life of children, adolescents, and young adults with neurofibromatosis type 1 and their families: Analysis of narratives

Abstract: Pediatric nurses should routinely assess for HRQoL in this population and develop strategies tailored to those concerns that require intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
3
13
0
Order By: Relevance
“…These results are consistent with previous previous studies, which showed individuals with NF experience decreased QoL in all subdomains of QoL [4, 9, 19, 20, 23–25]. The studies have outlined a framework that included five domains reflecting the most important concerns: physical function impact, bodily pain, social functioning, sigma, and emotional distress [36]. A review study on functioning, disability and health in children with neurofibromatosis type 1 provided a beginning understanding of some QoL concerns from the perspectives of youth and their families [37].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with previous previous studies, which showed individuals with NF experience decreased QoL in all subdomains of QoL [4, 9, 19, 20, 23–25]. The studies have outlined a framework that included five domains reflecting the most important concerns: physical function impact, bodily pain, social functioning, sigma, and emotional distress [36]. A review study on functioning, disability and health in children with neurofibromatosis type 1 provided a beginning understanding of some QoL concerns from the perspectives of youth and their families [37].…”
Section: Discussionsupporting
confidence: 91%
“…In this study the patients and their families were most concerned about physical functioning, pain, appearance/disfigurement, social activity/role participation, stigma, anxiety and social relationships [38]. Another study conducted based on semi-structured interviews revealed additional areas of concern including cognitive functioning, family impact, and treatment burden [36]. Our findings and these results suggest that NF is a broad spectrum disease that represents a considerable burden for patients, affecting all aspects of life.…”
Section: Discussionmentioning
confidence: 99%
“…Children and adults with NF1 report a lower QoL in physical and mental domains (Vranceanu, Merker, Park, & Plotkin, 2013). The majority of studies exploring QoL in NF1 have been performed in children; all have demonstrated a diminished quality of life (Domon‐Archambault, Gagnon, Benoit, & Perreault, 2018; Draucker, Nutakki, Varni, & Swigonski, 2017; Graf, Landolt, Mori, & Boltshauser, 2006; Krab et al., 2009). Several studies have shown that child self‐reported QoL ratings were generally higher than parent and teacher reports, which may reflect cognitive deficits, self‐concept difficulties, or self‐protective mechanisms (Graf et al., 2006; Vranceanu, Merker, Park, & Plotkin, 2015).…”
Section: Genetic Counseling Processmentioning
confidence: 99%
“…A distinguishing feature of the present study is the utilization of NF1‐specific multi‐item measurement scales as predictor and mediator variables, which were developed explicitly for NF1 through extensive cognitive interviews with children, adolescents, and young adults with NF1 (Draucker, Nutakki, Varni, & Swigonski, ; Nutakki, Varni, Steinbrenner, Draucker, & Swigonski, ), rather than using generic measures for these variables. We suggest that using NF1‐specific predictor and mediator variables provides more precise targets for interventions to improve overall generic HRQOL as the item content for these NF1‐specific scales were developed from the perspective of and close collaboration with youth with NF1 (Draucker et al, ; Nutakki et al, ), and subsequently field‐tested for reliability and validity in a national validation study (Nutakki, Varni, & Swigonski, ).…”
Section: Introductionmentioning
confidence: 99%